Role of Probiotics in Mycoplasma pneumoniae Pneumonia in Children: A Short-Term Pilot Project - Ling, Zongxin; Liu, Xia; Guo, Shu; Cheng, Yiwen; Shao, Li; Guan, Dexiu; Cui, Xiaoshuang; Yang, Mingming; Xu, Xiwei (Frontiers in Microbiology, 2019)
Mycoplasma pneumoniae is one of the most common pathogens causing community-acquired pneumonia in children. Mycoplasma pneumoniae pneumonia (MPP) can be successfully treated with azithromycin; however, antibiotic-associated diarrhea (AAD) is a common adverse effect. Increasing evidence suggests that some probiotics may prevent the development of AAD. The present study determined the effects of probiotics (live Clostridium butyricum plus Bifidobacterium infantis) on the prevention and treatment of AAD in children with MPP when co-administered with intravenous azithromycin. Fifty-five consecutive children with MPP were enrolled and received azithromycin (10 mg/kg/day; once daily for 7 days) combined with probiotics (starting on the 3rd day of azithromycin treatment; 1500 mg three times daily); 50 healthy children served as controls. At the end of the trial, the incidence of AAD, fecal microbiota, intestinal mucosal barriers, and systemic inflammation were analyzed using recommended systems biology techniques. No cases of AAD or other adverse events occurred in children with MPP after co-administration of probiotics with azithromycin. A live C. butyricum plus B. infantis preparation partly reconstructed the gut microbiota, especially restoration of bacterial diversity. The indicators of intestinal mucosal barrier function, such as D-lactate, endotoxin, and diamine oxidase, were significantly improved and the systemic inflammation (interleukin 10) was attenuated after probiotic therapy. The present study indicated that co-administration of probiotics with azithromycin is a promising therapy for MPP treatment which could prevent and treat AAD effectively.